Measuring Rural Access : Update 2017/18 - World Bank (World Bank, Washington, DC, 2019)
Transport connectivity is an essential part of the enabling environment for inclusive and sustained growth. In many developing countries, particularly in Africa, most people are still not connected to local, regional, or global markets. Such rural accessibility is crucial to reduce poverty and promote inclusive economic growth. The Sustainable Development Goals (SDGs) aim to build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation (Goal 9), for which Target 9.1 is to ‘develop quality, reliable, sustainable and resilient infrastructure, to support economic development and human well-being, with a focus on affordable and equitable access for all.’ The Rural Access Index (RAI) was proposed and accepted as an indicator to measure this target. The RAI is one of the most important global indicators in the transport sector. It measures the proportion of people who have access to an all-season road within an approximate walking distance of 2 kilometers (km). There is a common understanding that the 2 km threshold is a reasonable extent for people’s normal economic and social purposes. The definition is also simple enough to understand and use not only in the transport sector, but also in the broader development context, such as poverty alleviation. The initial RAI study in 2006 was based on household surveys and other simplified methods, estimating the global index at 68.3 percent, leaving a rural population of about one billion disconnected around the world.